How to Stop Worrying and Start Living - Dale Carnegie (Pocket Books, 1984)
This book can change your life! Through Dale Carnegie\\\'s six-million-copy bestseller recently revised, millions of people have been helped to overcome the worry hobbit. Dale Carnegie offers a set of practical formulas you can put to work today. In the fast-paced world of the 1990\\\'s -- formulas that will last a lifetime! Discover how to: Eliminate fifty percent of business worries immediately Reduce financial worries Avoid fatigue -- and keep looking you Add one hour a day to your waking life Find yourself and be yourself -- remember there is no one else on earth like you! How to Stop Worrying and Start Living deals with fundamental emotions and ideas. It is fascinating to read and easy to apply. Let it change and improve you. There\\\'s no need to live with worry and anxiety that keep you from enjoying a full, active and happy life!